2016
DOI: 10.17503/agrivita.v38i2.502
|View full text |Cite
|
Sign up to set email alerts
|

Rice Ratoon Yield Response to Main Crops Cutting Height in Tidal Swamp Using Direct Seeding System

Abstract: This study was aimed to evaluate the effect of main crops harvest cutting height on the yield of rice ratoon in the tidal swamp by using direct seeding system. The experiment was conducted in Telang Sari village, District of Tanjung Lago, Banyuasin, South Sumatra Province from November 2013 to April 2014. It measured plots 4 x 5 m through a randomized block design with 5 replications. The treatment was main crops harvest cutting height of 10, 20, 30, 40 and 50 cm above the soil surface. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
4
10
0
1
Order By: Relevance
“…There does not seem to be a consensus on a suitable cutting height to produce a high‐yielding second crop when using the ratoon methods. Some previous studies reported that appropriate cutting height of the first crop for producing higher grain yield of the second crop was 20 cm in Louisiana and Florida (Harrell, Bond, & Blanche, 2009; Jones, 1993), whereas other studies reported that it was 40 cm in Sari, India, and South Sumatra, Indonesia (Mareza, Djafar, Suwignyo, & Wijaya, 2016; Shahri et al., 2012). A more recent modeling study showed that a suitable cutting height of the first crop was 40 cm in China (Ling et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There does not seem to be a consensus on a suitable cutting height to produce a high‐yielding second crop when using the ratoon methods. Some previous studies reported that appropriate cutting height of the first crop for producing higher grain yield of the second crop was 20 cm in Louisiana and Florida (Harrell, Bond, & Blanche, 2009; Jones, 1993), whereas other studies reported that it was 40 cm in Sari, India, and South Sumatra, Indonesia (Mareza, Djafar, Suwignyo, & Wijaya, 2016; Shahri et al., 2012). A more recent modeling study showed that a suitable cutting height of the first crop was 40 cm in China (Ling et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Susilawati et al (2012) stated that the height and number of productive tillers for ratoon rice in genotype IPB106-F-8-1 at a 10 cm cutting was higher than that at 20 cm and 30 cm cuttings. Mareza et al (2016) stated that cutting 40 to 50 cm of the main rice stem was significant for the number of productive tillers, with the highest found at the 40 cm cutting (6.55 tillers) compared to the other cutting sizes.…”
Section: Discussionmentioning
confidence: 99%
“…which was 108.0 grains higher than the 20 cm and 30 cm cuttings (78.5 and 71.1 grains, respectively). Mareza et al (2016) stated that cutting 10 cm of the rice stems significantly improved the panicle length and the number of grains per panicle of ratoon rice by 14.93 cm and 47.05 grains, respectively, compared to the cuttings of 20 to 50 cm.…”
Section: Discussionmentioning
confidence: 99%
“…This condition may be due to the differences in total assimilates in the stubbles after harvesting the main crop. Stubble of rice plants that grow back after harvest and produce new tillers and grain which can be harvested (Islam et al, 2008;E Mareza et al 2016).…”
Section: Vegetative Growthmentioning
confidence: 99%